Antigen‐triggered interferon‐γ and interleukin‐10 pattern in cured mucosal leishmaniasis patients is shaped during the active phase of disease. (September 2014) - Nogueira, R. S.; Gomes‐Silva, A.; Bittar, R. C.; Silva Mendonça, D.; Amato, V. S.; da Silva Mattos, M.; Oliveira‐Neto, M. P.; Coutinho, S. G.; Da‐Cruz, A. M.
Summary An exacerbated type 1 response to leishmanial antigens is the basis of tissue destruction observed in mucosal leishmaniasis (ML). After therapy, a persistent production of high levels of inflammatory cytokines can confer a poor prognosis. Herein we investigated whether the clinical conditions defined during the active phase of ML affect the magnitude of long‐term anti‐Leishmania immune response. Twenty clinically cured ML cases were studied. Peripheral blood mononuclear cells (PBMC) were cultured with L. braziliensis antigens (Lb‐Ag), Toxoplasma gondii antigens (Tg‐Ag), concanavalin‐A (Con‐A) or medium alone, and the lymphocyte proliferative response and cytokine secretion were quantified. Medical records were reviewed for Montenegro skin test (MST) during diagnosis, duration of ML disease or time elapsed after clinical cure. The duration of disease was correlated positively with MST (r = 0·61). Lb‐Ag induced interferon (IFN)‐γ was correlated positively with duration of illness (r = 0·69) as well as the frequency of secreting cells [enzyme‐linked immunospot (ELISPOT)] assay. No association was observed for Tg‐Ag or Con‐A. Disease duration was correlated negatively with interleukin (IL)‐10 production (r = −0·76). Moreover, a negative correlation between length of time after clinical cure and TNF levels (r = −0·94) or the IFN‐γ : IL‐10 ratio (r = −0·89) were also seen. We suggest that the magnitude of the IFN‐γ inflammatory response triggered by ML can be driven by the time of leishmanial antigens exposition during the active phase of the disease. This pattern could persist even long‐term after cure. However, despite IFN‐γ levels, the decrease of the TNF and IFN‐γ : IL‐10 ratio reflects the control of proinflammatory responses achieved by cure of ML, possibly preventing disease relapses.